Personality and Psychological Adjustment of Greek-Cypriot Youth in the Context of the Parental Acceptance-Rejection Theory - Demetriou, Loucia; Christodoulides, Paul (My University, 2011)
Research reported here is based on Rohner’s personality sub theory component of the Parental Acceptance-Rejection Theory (PART) of Socialisation: Perceived parental rejection has consistent negative effects on the psychological adjustment of children and adults worldwide (Rohner and Khaleque, 2008). As part of a research project on antisocial behaviour of Cypriot youth we postulated the hypothesis that the individual’s overall psychological adjustment (comprised and represented by the Total Composite Test Score and the scores on the seven scales of the Personality Assessment Questionnaire – PAQ), can predict antisocial behaviour in form of racistic tendencies in a given population. We tested 1,185 Greek Cypriots (aged 15-23 years) using PART’s Personality Assessment Questionnaire (PAQ) and other especially developed questionnaires. Here we present the findings of the initial stages of our research, namely the analysis of the responses of the Greek Cypriot sample on the Adult-PAQ scales. The majority of the Greek Cypriot respondents were found to be in the zone of good emotional and behavioural functioning. These findings, paired with the results of the Cyprus Child PARQ for high perceived acceptance and low rejection in childhood (Demetriou and Christodoulides, 2006) seem to confirm Rohner’s postulates in the Parental Acceptance Rejection personality sub theory.
Keywords: Parenting styles; Parental Acceptance-Rejection; Personality functioning